Performance of potato (Solanum tuberosum) advanced hybrid MS/6-1947 under high temperature stress and water deficit conditions - LUTHRA, S K; RAWAL, SANJAY; GUPTA, V K; MALIK, KAMLESH (The Indian Journal of Agricultural Sciences, 2018)
In present investigation, potato (Solanum tuberosum L.) advanced stage hybrid MS/6-1947 was evaluated along with controls under high temperature and water stress regimes for three successive winter crop seasons. Under high temperature at Modipuram, MS/6-1947 (13.3 t/ha) showed yield enhancement of 20, 9 and 11% over the controls Kufri Bahar, Kufri Pukhraj and Kufri Surya. It also exhibited at par tolerance to hopper with Kufri Surya and damages due to mite burn were lower than Kufri Bahar and Kufri Pukhraj. The hybrid possessed 18% tuber dry matter. Results ondrought toleranceat Modipuram revealed superior performance of MS/6-1947 under normal irrigation, mild water and severe water stress conditions as compared to best control Kufri Pukhraj as yield reduction was comparatively lower under mild and severe water stress treatments. Drought tolerance index (DTI) values were maximum in MS/6-1947 (1.02 and 0.79) followed by Kufri Pukhraj (0.86 and 0.51) and Kufri Bahar (0.72 and 0.58) under mild and severe water deficit treatments, respectively. Drought tolerance studies at Jodhpur revealed better performance of MS/6-1947 under normal and mild water stress conditions as compared to the controls Kufri Pukhraj and Kufri Surya as yield reduction was comparatively lower under mild water stress conditions. DTI values were maximum in MS/6-1947 (1.08) followed by Kufri Puhkraj (1.01) and Kufri Surya (0.41) under mild water deficit treatment. Tuber dry matter content increased under water stress over normal irrigation at both the locations. MS/6-1947 is suitable for table potatoes. MS/6-1947 may be a better option for integrating in cereal based crop sequences, for exploiting its yield potential in early season and for attaining sustainable productivity in areas where high temperature and lower water availability are constraint for raising the successful potato crop.